2018
DOI: 10.1080/21691401.2017.1423497
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial anti-inflammatory effect of paeonol self-microemulsion-loaded colon-specific capsules on experimental ulcerative colitis rats

Abstract: Paeonol, as the main phenolic compound isolated from the Chinese herbs, has been confirmed to present anti-inflammatory effects on ulcerative colitis (UC) in our previous study. However, its poor solubility has hindered its development of being a favourable pharmaceutical product in treating colon diseases. In this study, we prepared the colon-specific delivery system (Pae-SME-CSC) with paeonol-loaded self-microemulsion (Pae-SMEDDS), and evaluated its in vitro and in vivo properties, especially the anti-inflam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 73 publications
0
9
0
Order By: Relevance
“…Forty-eight male Wistar rats weighing 200 + 20 g were randomly set in six groups of eight rats each. The rats were acclimatized to the animal house conditions (12-h lighting cycle and 25 + 2 C temperature) for 1 week and then arranged as normal control, paeonol control (200 mg/kg orally), 16 ulcer model IND (50 mg/kg orally) 15 -treated, IND/paeonol (50 mg/kg orally) 12 -treated, IND/paeonol (200 mg/kg orally)-treated, and positive control ranitidine (50 mg/kg orally) 17 -treated groups. Both paeonol and ranitidine were administered once daily for 3 days before ulcer induction.…”
Section: Animals and Experimental Proceduresmentioning
confidence: 99%
“…Forty-eight male Wistar rats weighing 200 + 20 g were randomly set in six groups of eight rats each. The rats were acclimatized to the animal house conditions (12-h lighting cycle and 25 + 2 C temperature) for 1 week and then arranged as normal control, paeonol control (200 mg/kg orally), 16 ulcer model IND (50 mg/kg orally) 15 -treated, IND/paeonol (50 mg/kg orally) 12 -treated, IND/paeonol (200 mg/kg orally)-treated, and positive control ranitidine (50 mg/kg orally) 17 -treated groups. Both paeonol and ranitidine were administered once daily for 3 days before ulcer induction.…”
Section: Animals and Experimental Proceduresmentioning
confidence: 99%
“…Moreover, we prepared the colon-specific delivery system (Pae-SME-CSC) with paeonol-loaded self-microemulsion (Pae-SMEDDS), and evaluated its properties in vitro and in vivo, especially the anti-inflammatory effects on UC rats. It indicated that the developed Pae-SME-CSC was suitable for colon-specific drug delivery [ 70 ].…”
Section: Pharmaceutical Strategiesmentioning
confidence: 99%
“…Treatment of IBD continue to be challenging despite of advancements in research being carried out. For several years, strategies like development of microspheres [47], liposomes [48], microemulsions [49], nanocores [50], etc. have been adopted for targeted delivery of drug in the treatment of IBD.…”
Section: Histopathological Studiesmentioning
confidence: 99%